Safeguarding Bukoba Oral Tradition Through Communal Copyright and Local Regulation: A Normative-Empirical Study in Rokan Hulu Regency, Indonesia - Kurniawansyah, Dani; Hendri, Hendri; Syahroni; Muhammad Arsy Ash Shiddiqy; Yanto, Budi (Journal of Law, Politic and Humanities, 2026)
Bukoba, an oral tradition of Rokan Hulu Regency, represents a living form of Malay cultural expression yet remains vulnerable to extinction due to the absence of legal recognition and system-atic documentation. Methods: This study applies a normative empirical legal approach by combining statutory analysis of Indonesia’s Copyright Law No. 28 of 2014 and UNESCO’s 2003 Convention with field data obtained through interviews with local cultural actors and the Rokan Hulu Tourism Office. Results: Findings indicate that Bukoba has not been included in the regional intangible cultural heritage inventory, leading to a lack of communal copyright protection and policy attention. The gap arises from limited institutional coordination, insufficient funding, and low community legal awareness. Conclusions: The research proposes an integrated safeguarding framework encompassing (i) digital documentation as legal evidence of collective ownership, (ii) community-based transmission and legal literacy programs, and (iii) enactment of local regula-tions to institutionalize protection measures. The model demonstrates that effective preservation of oral traditions requires synergy between legal instruments and local participation to ensure sustainability and prevent cultural misappropriation